2014
DOI: 10.29252/ijn.27.90.91.14
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Self-esteem in Fertile and Infertile Women

Abstract: Background & Aim: Childbearing is one of the purposes of marriage and having no child could have a negative impact on various aspects of women's lives. The aim of this study was to compare the self-esteem of fertile and infertile women. Material & Methods: It was a descriptive cross-sectional study that was carried out among 200 fertile and infertile women (100 fertile and 100 infertile) referred to the Research Centre for Reproductive and gynecological clinic of Shahid Beheshti University of Medical Sciences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2020
2020
2121
2121

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…The mean of participants' age was 30.70 ± 4.27 in the intervention group and 32.43 ± 5.37 in the control group and the between-group difference was not significant. Two previous studies reported significant inverse correlation between age and SE among infertile couples (4) and infertile women (14). Our findings also showed that most participants in the intervention group (73.3% of women and 66.7% of men) and the control group (66.7% of women and 73.3% of men) had secondary diploma and the between-group difference was not significant.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The mean of participants' age was 30.70 ± 4.27 in the intervention group and 32.43 ± 5.37 in the control group and the between-group difference was not significant. Two previous studies reported significant inverse correlation between age and SE among infertile couples (4) and infertile women (14). Our findings also showed that most participants in the intervention group (73.3% of women and 66.7% of men) and the control group (66.7% of women and 73.3% of men) had secondary diploma and the between-group difference was not significant.…”
Section: Discussioncontrasting
confidence: 46%
“…Moreover, most male participants in these groups were self-employed (53.3% vs. 60%) with no significant between-group difference. A previous study into the SE of fertile and infertile women also showed that 67% of fertile women and 70% of infertile women were housewife (14). Another study reported that employed women had higher SE than housewife women (25).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, self-efficacy is a critical characteristic to cope with infertility (Ebrahimifar et al 2018). Numerous studies reported a decline in the self-efficacy of infertile women due to low self-esteem (Zare, Bahrami & Soleimani 2014;Moghaddam Tabrizi & Feizbakhsh 2015), high levels of stress (Ebrahimifar et al 2018), poor mindfulness, and emotional intelligence (Heidari & Latifnejad 2010), poor psychological wellbeing (Mazaheri & Bahramian 2016), and poor mental health (Hosseini et al 2018). Therefore, therapies designed to improve self-efficacy are closely associated with self-esteem, stress reduction, mindfulness, emotional intelligence, psychological wellbeing, and mental health.…”
Section: Introductionmentioning
confidence: 99%